Lipid Metabolism Crosstalk in the Brain: Glia and Neurons - Barber, Casey N.; Raben, Daniel M. (Frontiers in Cellular Neuroscience, 2019)
Until recently, glial cells have been considered mainly support cells for neurons in the mammalian brain. However, many studies have unveiled a variety of glial functions including electrolyte homeostasis, inflammation, synapse formation, metabolism, and the regulation of neurotransmission. The importance of these functions illuminates significant crosstalk between glial and neuronal cells. Importantly, it is known that astrocytes secrete signals that can modulate both presynaptic and postsynaptic function. It is also known that the lipid compositions of the pre- and postsynaptic membranes of neurons greatly impact functions such as vesicle fusion and receptor mobility. These data suggest an essential lipid-mediated communication between glial cells and neurons. Little is known, however, about how the lipid metabolism of both cell types may interact. In this review, we discuss neuronal and glial lipid metabolism and suggest how they might interact to impact neurotransmission.